Evaluating healthy cities: A scoping review protocol. - Michelle Amri; Safa Ali; Geneviève Jessiman-Perreault; Kathryn Barrett; Jesse Boardman Bump (PLoS ONE)
Background The Healthy Cities project supports municipal policymakers in the struggle to safeguard the health of urban citizens around the world (and in other limited geographies such as islands). Although Healthy Cities has been implemented in thousands of settings, no synthesis of implementation experiences have been conducted. In this article, we develop a scoping review protocol that can be applied to collect evidence on process evaluations of Healthy Cities. Methods To develop a scoping review protocol that could identify experiences evaluating the Healthy Cities project, we followed the PRISMA guidelines for Scoping Reviews (PRISMA-ScR). We applied these guidelines in consultation with a research librarian to design a search of the peer-reviewed literature, specifically Ovid Medline, Ovid Embase, Web of Science Core Collection, and Scopus databases, and a grey literature search. Discussion In addition to the aim of collecting evidence on Healthy Cities process evaluation experiences, the broader goal is to spark discussions and inform future evaluations of Healthy Cities. This work can also inform other evaluations of initiatives seeking to raise socio-political change, such as those focused on enhancing intersectoral and multisectoral action.